Analysis of Capital Assistance for Micro Enterprises by the Service of Cooperatives and SMEs - Fathur Rahman Baihaki; Mustapa Khamal Rokan (Penerbit Jurnal Indonesia, 2022)
Micro, small, and medium enterprises are one of the main pillars of the national economy that must o tain the main opportunity, support, protection, and development as widely as possi le as a form of firm alignment with people's economic usiness groups, without neglecting the role of large usinesses and State-Owned Enterprises. One of the o stacles in developing micro-enterprises is limited capital and limited access to sources of capital. This research is a case study of micro usiness group capital assistance y the Department of Cooperativen andnSMEs, Mandailing Natal Regency. The purpose of this research is to analyze the differences in capital, sales turnover, and profits of micro usinesses that receive capital assistance. The approach used is a qualitative approach. The population in this study is a mem er of the group of micro usiness actors (KPUM) in Panya ungan Kota District who received capital assistance amounting to 30 people. This study shows that capital assistance from the Cooperatives and UKM Service can help micro-enterprises in Panya ungan District to increase capital, sales turnover, and profits, which refers to the varia les of capital differences, sales turnover, and profits after seeing efore and after o taining a loan. This means that the government's loan program through loan provisions can help develop micro-enterprises.